2016
DOI: 10.1186/s12906-016-1413-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root-extracts of Ficus benghalensis (Banyan) in memory, anxiety, muscle co-ordination and seizure in animal models

Abstract: BackgroundFicus benghalensis L. (Banyan) is a commonly found tree in Eastern Nepal. Its different plant parts are used for various neurological ailments. This study was performed in mice to see its effects in various neuropharmacological parameters.MethodsPassive-avoidance (memory), Open-field (anxiety), Pentobarbital-induced Sleep potentiation (sleep), Rota-rod (muscle-co-ordination), Pentylenetetrazol-Induced and Maximal Electroshock Seizure Tests were performed. Sample size was calculated using G*Power 3.1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Recent scientific studies have demonstrated anti-inflammatory potency on adjuvant induced arthritis [23] and antioxidant effects of Ficus benghalensis [23]. When tested in albino mice, extracts of aerial roots demonstrated better cognition, muscular relaxation and seizure reduction [24]. Different parts of Ficus benghalensis L have been known traditionally to resolve ailments related to the central nervous system [25] and many researchers have described various neuropharmacological effects of this plant [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific studies have demonstrated anti-inflammatory potency on adjuvant induced arthritis [23] and antioxidant effects of Ficus benghalensis [23]. When tested in albino mice, extracts of aerial roots demonstrated better cognition, muscular relaxation and seizure reduction [24]. Different parts of Ficus benghalensis L have been known traditionally to resolve ailments related to the central nervous system [25] and many researchers have described various neuropharmacological effects of this plant [26].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of various plant parts of F. benghalensis have been known for their anathematic, analgesic, anti-inflammatory, antioxidant, antidiabetic, immuno-modulatory, and antimicrobial activities since ancient times, and the prop root has been used for toothaches. The stem, leaf, bark, fruit, and sap extracts of F. benghalensis have been used as an ayurvedic medicines to cure various diseases like dysentery, teeth disorders, skin disorders like sores, piles, diarrhea, and rheumatism, and to boost the immune system (Nidhiya et al 2010;Kumar et al 2010;Panday and Rauniar 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the group effect on repeatedly measured behavioral parameters were tested using Repeated Measurement ANOVA [SPSS (United States)]. Non-parametric tests were chosen because a normal distribution (Shapiro-Wilk test) could not always be assumed (Sajikumar et al, 2007; Salkovic-Petrisic et al, 2015; Panday and Rauniar, 2016). P -value with <0.05 was considered to indicate a statistically significant difference between two groups and presented in the text.…”
Section: Methodsmentioning
confidence: 99%